Changes in the incidence of African cassava mosaic geminivirus and the abundance of its whitefly vector along southnorth transects in Uganda - Legg, James P.; Ogwal, S. (1998)
Surveys of the incidence of African cassava mosaic disease (ACMD) and its whitefly vector, Bernisiu tabaci, were made at three-month intervals in 1992 and 1993 along two South-North transects. One was in central and the other in eastern Uganda. ACMD incidence was high within the northern localities of each transect and low towards the south. Incidence increased over the period at localities on the ACMD epidemic 'front' which was the interface between high incidence areas to the north and low incidence areas to the south. Combining data for both transects, the relationship between 'infective potential' (the product of whitefly number and the incidence of ACMD attributed to the use of infected cuttings, 'x') and the increase in proportion of infected plants caused by whiteflies ('y', as transformed to account for multiple infection) was described by the straight line regression: y = 4 7 . 8x + 9.2 (F ratio = 63.0, r2 = 0.78). This emphasises the importance for control of reducing ACMD incidence by phytosanitation and/or use of resistant varieties since reduction of whitefly numbers is not easily achieved. Possible mechanisms for the expansion of the ACMD epidemic and implications of the study findings for control of ACMD are discussed.